In planta Activity of the Novel Copper Product HA + Cu(II) Based on a Biocompatible Drug Delivery System on Vine Physiology and Trials for the Control of Botryosphaeria Dieback - Mondello, Vincenzo; Fernandez, Olivier; Guise, Jean-François; Trotel-Aziz, Patricia; Fontaine, Florence (Frontiers in Plant Science, 2021)
The growing concerns on human and environment health are forcing the plant protection industry towards the formulation of more eco-sustainable plant protection products (PPP), both efficient and innovative in their approach to disease control. A large number of these innovative formulations now rely on a combination of pathogens antagonistic properties and stimulation of natural plant defense to pathogens. The formulation HA+Cu(II), in which copper is delivered to the plants by the drug-delivery molecule hydroxyapatite (HA), was found efficient against the grapevine pathogens Plasmopara viticola and Phaeoacremonium minimum and able to induce the host-plant defense system. We investigated the HA+Cu(II) impacts on grapevine physiology, both in uninfected and when infected by the Botryosphaeria dieback agents Diplodia seriata and Neofusicoccum parvum. This study of plant physiology and disease impact were addressed to evaluate both the HA+Cu(II) potential as a plant defense elicitor and its possible and future use as PPP in vineyard. Our results showed that HA+Cu(II) induced several key-defense genes without negatively affecting plant growth and photosynthetic activity. In addition, fungistatic effect on the two Botryosphaeriaceae at the in planta tested concentrations is reported. Altogether, our results obtained under controlled conditions fully support the potential of HA+Cu(II) as a promising PPP towards grapevine trunk diseases in vineyard.